Investigating Algerian Use of English Modals: The Case of Second Year Master Students of English at the University “Frères Mentouri”, Constantine 1 - SELMEN, Salima (Journal of Human Sciences, 2018)
The acquisition and application of English modals in appropriate contexts are among the essential aspects of second and foreign language acquisition. Thus, the current study is carried out in order to investigate the use of English modal verbs by Algerian university learners of English. The study is intended to identify to what extent the participants could acquire the functional properties of modal verbs. It also explores the most challenging aspects in the acquisition of modal verbs. Our study is an attempt to shed more light on the proficiency level of learners’ performance in acquiring modal verbs. In order to fulfill the intended aims, 116 second year master students of English were assessed on their use of modals. The data analysis revealed that the students showed a low performance and faced some ambiguities in identifying the appropriate English modal.